SHOCK METAMORPHISM OF ENSTATITE CHONDRITES - Rubin A.E.; Scott E.R.D.; Keil K. (My University, 1997)
We have extended the shock-metamorphism classification scheme of Stoffler et al. (1991) to account for shock effects in orthopyroxene and applied it to sixty enstatite chondrites. Orthopyroxene exhibits the following sequence of progressive shock effects: shock stage S1 (unshocked), sharp optical extinction; S2 (very weakly shocked), undulose extinction; S3 (weakly shocked), development of clinoenstatite lamellae parallel to (100); S4 (moderately shocked), weak mosaicism; S5 (strongly shocked), strong mosaicism. As in the Stoffler et al. (1991) scheme, stage S5 is characterized principally by the solid-state transformation of crystalline plagioclase into maskelynite.Most EL3 chondrites exhibit foliations caused by impact deformation of chondrules and metal particles. EL5 and EL6 chondrites are all shock stage S2. Because opaque veins are rare in S2 ordinary chondrites, it is plausible that the centimeter-size kamacite veins in Atlanta and Blithfield and the 1.6-cm-long oldhamite-rich vein in Jajh deh Kot Lalu (all EL6) formed when their hosts were shocked to S3-S5 levels. Because removal of shock-stage S3-S5 features (including repair of shock-damaged orthopyroxene) requires levels of metamorphism comparable to those experienced by petrologic type-5 to -6 chondrites, we infer that proto-EL6 material was shocked to S3-S5 levels prior to peak metamorphism and shocked again to stage S2 after metamorphism. Overall, enstatite chondrites appear to have suffered greater shock damage than ordinary and carbonaceous chondrites.